AGRESI MILITER BELANDA II DI SUNGAI APIT KABUPATEN SIAK TAHUN 1948-1949 - Mutmainah, Mutmainah; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absrtak: The independence achieved by the Indonesian people proclaimed on August 17, 1945, is not the end of the Indonesian struggle against Dutch colonialism. The Dutch returned to take control of Indonesia, so that the Indonesian nation still had to struggle to maintain the independence that had been achieved. To regain control of the Netherlands using both diplomacy and attack methods. The attacks occurred in various regions including the Sumatran region, one of which was in the Sungai Apit. The purpose of this study was 1) To determine the condition of the Sungai Apit before the Second Dutch Military Aggression , 2) To find out the background of the occurrence of Second Dutch Military Aggression in Sungai Apit, 3) To find out the process of the Second Dutch Military Aggression in Sungai Apit, 4) To knowing the end of Second Dutch military aggression on the Sungai Apit. The research uses qualitative methods with a historical approach with data collection techniques, namely interviews, observation, documentation and decision-making. The results of this study are the occurrence of Second Dutch military aggression on the Sungai Apit against the backdrop of several events and conditions of the region that are very strategic because they are located on the mouth of the river where the traffic lane is located. The outbreak of Dutch Military Aggression on the Sungai Apit resulted in a clash between the Dutch army and the Indonesian side and the burning in the town of Sungai Apit by the Dutch. The role of the national heroes and the previous people in their struggle to defend Indonesian independence is so great that we should respect and appreciate their services and take care and not forget the history that exists in this country.Key Words: Second Dutch military aggression, history, Sungai Apit